Impact of dehulling, germination and fermentation on the bioactive and functional properties of grey pea flour - Amanipour, Armaghan; Samaei, Yasaman; Böök, Olof; Granfeldt, Yvonne; Lazarte, Claudia E. (Frontiers in Nutrition, 2024)
Grey pea is a largely overlooked legume in the Nordic countries, and its potential uses in various food products remain largely unexplored. It is a nutrient-rich crop with low environmental impact, making it an attractive option for sustainable and nutritious plant-based alternatives. This research investigated the impact of dehulling, germination, and fermentation on the bioactive (polyphenol content and antioxidant capacity) and functional characteristics (water absorption index, water solubility index, water and oil binding capacity, emulsifying and gelation concentration) of grey pea flour. Additionally, protein content and pasting properties (temperature, peak viscosity, trough viscosity, breakdown, final viscosity, and setback) were measured. Dehulling was done using a runner disk sheller. Germination was performed for 24 and 48 hours at ambient temperature and fermentation was conducted for 8 hours at 43℃ using a starter culture. Results indicate that dehulling did not significantly affect functional properties and gelling capacity (p=0.297 for oil absorption capacity, p=0.5 for emulsion activity, and p=0.607 for emulsion stability) but resulted in a notable decrease in total polyphenol content (TPC) and antioxidant capacity (TAC). Conversely, 48 hours of germination increased TAC by two methods: FRAP (19%) and DPPH (30%). This process increased the through viscosity by 1.2-fold, while it did not significantly affect the water absorption index (WAI), water solubility index (WSI), or the emulsifying properties of grey pea flour. Fermentation significantly improved TPC (p<0.001 for whole grey peas and p=0.004 for dehulled grey peas), with an TPC increase up to 67% in fermented dehulled pea flour. TAC measured by both methods, also showed significant increases, ranging from 35% to 104%. However, fermentation reduced emulsifying and pasting properties, as indicated by the peak, through and final viscosity, which may be desirable only for certain food products. Further, germination and fermentation showed small but significant increases in protein content, by 4 and 8% respectively. Fermented grey pea flour exhibited enhanced bioactive characteristics, while 48-hour germination positively impacted pasting properties. Overall, these processes led to changes in both the bioactive and functional properties of grey pea flour, creating opportunities for the use of these flours in a wide array of food products.